2019
DOI: 10.1111/bcpt.13287
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of Psoralen and Isopsoralen hepatotoxicity as revealed by hepatic gene expression profiling in SD rats

Abstract: Background The main bioactive components of Fructus psoraleae, such as psoralen and isopsoralen, are known to be hepatotoxic. However, its underlying mechanism is to be elucidated. Methods To address this, SD rats were randomly divided into control group, 60 mg/kg psoralen group and 60 mg/kg isopsoralen group. Blood was collected to detect serum biochemical indices. RNA was extracted from liver samples, and then, cDNA gene expression profiles were analysed. Results Psoralen administration significantly up‐regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Psoralen was deemed to be innoxious at low doses in previous publications. 30,31 Also, a recent clinical study reported that low-dose and low-frequency oral psoralen−UV-A treatment are effective to treat early-stage mycosis fungoides. 32 However, other reports suggested that the effect of drug accumulation in the body should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Psoralen was deemed to be innoxious at low doses in previous publications. 30,31 Also, a recent clinical study reported that low-dose and low-frequency oral psoralen−UV-A treatment are effective to treat early-stage mycosis fungoides. 32 However, other reports suggested that the effect of drug accumulation in the body should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…The results inspired us that the long-term exposure might induce accumulated psoralen in the body and injure metabolic enzymes. We have previously found that psoralen and isopsoralen injured the liver through dislocating the cytochrome P450 metabolism [25], which maybe the main targets of psoralen and isopsoralen in the body. However, in the recovery period, all the damage were abolished except for the increases of AST (14 mg/kg, P < 0.05) and BUN (14 and 28 mg/kg, P < 0.01 and P < 0.05, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Song et al found that psoralen may induce liver injury in rats through the cytochrome P450 metabolic pathway of xenobiotics, among which Akr7a3, Gstm1, Cyp1a2, and Cyp1a1 are important genes in hepatotoxicity, and the endoplasmic reticulum is the principal target subcellular structure. It has been suggested that various cancers and metabolic conditions might be susceptible to hepatotoxicity induced by psoralen (Song et al, 2019). Wang et al demonstrated that psoralen inhibited the activity and protein expression of CYP2E1 (Wang et al, 2012).…”
Section: Liver Damagementioning
confidence: 99%